Description of Ceratogeusis thamiresae new genus and species from Panama, the first Telegeusinae (Coleoptera, Elateroidea, Omethidae) with flabellate antennae - Vinicius S. Ferreira (Contributions to Entomology)
Ceratogeusis thamiresae Ferreira, gen. et sp. nov., the first Telegeusinae with flabellate antennae, is described from Panama. The new genus and species is diagnosed and illustrated, and an updated key for the genera of Telegeusinae is given. The Telegeusinae genus Platydrilus López-Pérez & Zaragoza-Caballero, 2021, was discovered to be a junior homonym of Platydrilus Michaelsen, 1891 (Annelida, Oligochaeta, Eudrilidae), and therefore a pre-occupied name.